(untitled) (American Journal of Islam and Society, 2016)
On May 3, 2016, at the International Institute of Islamic Thought’s headquarters in Herndon, VA, Asaad Al-Saleh (Indiana University; scholar-in-residence, IIIT) spoke on “ISIS and Islam: How a Terrorist’s Ideology Twists Religion.” He began by asking a question – Is ISIS Islamic or not? – and then proceeded to give a “simple point of view.” He first drew a distinction between “Islam” and “Muslim,” which he said is a very problematic thing to do. “Islam” is the text (i.e., the Qur’an and the Hadith literature). He contended that the battle with ISIS is mainly textual, for the Qur’an is a “textual container.” Thus, anything beyond the Qur’an and Hadith texts cannot be considered purely Islamic, but only a human interpretation of the text. For example, if we take history, then “Islamic history” is a highly misrepresented label, for it is only “Muslims” who are participating in “history.” This historical error dates from the third Islamic century, with the rise of the “Islamic sciences.” As ISIS is not textually Islamic, not a revealed entity from the heaven of Islam, it cannot be labeled “Islamic” without violating the boundaries of the Qur’an and Hadith. On the second level, if ISIS claims to be a Muslim body interpreting Islam, then its members are not following the agreed-upon rules of interpretation. For example, their selective interoperations not only work against the majority of Muslims, including the scholars of Islam, but they are also being labeled as “deviant” even by other terrorist groups, such as al-Qaeda ...